Time-restricted feeding leads to sex- and organ-specific responses in the murine digestive system - Lalita Oparija-Rogenmozere; Madeleine R. Di Natale; Billie Hunne; Ada Koo; Mitchell Ringuet; Therese E. Fazio Coles; Linda J. Fothergill; Rachel McQuade; John B. Furness (PLoS ONE, 2025)
Food intake is a key regulator of the digestive system function; however, little is known about organ- and sex-specific differences in food-driven regulation. We placed male and female C57Bl/6 mice on time-restricted feeding (TRF), limiting access to food to an 8-hour window. Food was added either at dark (ZT12) or light (ZT0) onset for 14 days. Afterwards, the feeding period was delayed by 4 hours for half the mice, and the respective TRF regime continued for another 14 days. TRF from ZT12 to ZT20 led to the highest weight gain in females and the lowest in males, while improving intestinal transepithelial resistance (TEER) in both sexes. However, it also diminished food-anticipatory gene expression of several hepatic genes, particularly in female mice. Shifting food access to ZT16 increased weight gain and reduced fasting glucose levels in male mice, while also inducing strong food-driven gene expression changes in hepatic and duodenal tissues in both sexes. Feeding during the early lights-on phase (ZT0-ZT8) caused only minor physiological changes. However, it led to an overall downregulation of hepatic and an upregulation of duodenal and gastric gene expression and blunted the food-anticipatory expression response in both sexes. Delaying feeding until ZT4 was highly detrimental, reducing TEER and further disrupting gene expression in the stomach and liver in both sexes. In contrast, at least partial restoration of food-driven gene expression was seen in the duodenum, particularly in males. These findings highlight the strong sex- and organ-specific effects of food intake time on physiological and gene expression responses. Notably, we observed a lack of alignment in gene-expression responses between the gut and liver, underscoring tissue-specific sensitivity to feeding cues.